Telomeric attrition with increasing age in short- (Chihuahua dog) and long- (Asian elephant) life span animals - Kittisak Buddhachat (2018)
© 2017, Veteriner Fakultesi Dergisi. All rights reserved. Here, we explored the rate of telomere attrition with increasing age by real-time quantitative PCR (qPCR) in a short- (Chihuahua dog) and long(Asian elephant) lived species. A total of 122 Asian elephants (female = 106, male = 16) ranging from 24-840 months of age, and 89 Chihuahuas (female = 65, male = 24) 1-179 months of age were used in this study. We found that young (pre- and peri-pubertal) Asian elephants had a higher relative telomere length (RTL) compared to dogs. A low, but significant negative relationship between RTL and increasing age was observed in both Chihuahuas (R2=0.0490, P=0.0017) and Asian elephants (R2=0.0177, P=0.0210). The estimated rate of telomere loss for males and females of both species ranged from -0.0023 to -0.0065, with no clear differences between gender or species. Results suggest that Asian elephants may start with longer telomeres than Chihuahuas, as RTL was higher, but then the rate of telomere attrition proceeds at a similar rate in both species. Age accounted for only a small percentage of the variation in RTL in both Chihuahua dogs and Asian elephants, however. Thus, its use as a biological tool for age estimation would appear to be limited for these species.